PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) DI KELAS V SEKOLAH DASAR - Oktavia, Dea; Oktavia, Maharani; Ayurachmawati, Puji (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to create a valid and practical Higher Order Thinking Skills (HOTS) based Student Worksheet (LKPD) on cultural and national diversity material in Indonesia on learning Pancasila and Citizenship Education (PPKn). The method used in this research is the ADDIE Research and Development model with the stages of analysis, design, development, implementation and evaluation. Data were collected through observation, interview and questionnaire methods. The data analysis technique is carried out by carrying out validity analysis and practicality analysis. The analysis results obtained from research on the development of Student Worksheets (LKPD) based on Higher Order Thinking Skills (HOTS) are valid and practical with an average validity value of 83.3% which is categorized as very valid and an average practicality value of 90.7% in one to one trials and 94.7% in small group trials and were categorized as very practical. Based on the results of validation and trials, the LKPD developed is very valid and very practical as a learning facility for students. The created LKPD can be used as teaching material to improve students' critical thinking skills.